The Influence of Residence Hall Community on Academic Success of Male and Female Undergraduate Students. (2004)
Presents information on a study on the influences of gender and residence hall living on academic success of male and female undergraduate students in the U.S. Difference in patterns of involvement and interaction with peers and with the environment in their college community among males and females; Use of factor analysis and regression model in the study; Significance of self-assessment of academic progress in academic success.